Insecure Attachment Styles and Unbalanced Family Functioning as Risk Factors of Problematic Smartphone Use in Spanish Young Adults: A Relative Weight Analysis - Sonia Mangialavori; Claudia Russo; Maria Veronica Jimeno; Jorge Javier Ricarte; Giulio D'Urso; Daniela Barni; Marco Cacioppo (MDPI AG, 2021)
Young adulthood is the life stage during which people are more prone to develop problematic smartphone use (PSU). Only one study investigated the relationship among attachment styles, family functioning, and PSU, but thus far, no research has shown the relative importance that such dimensions may have on PSU. The main aim of this study was to analyze to what extent insecure attachment styles and unbalanced family functioning are related to PSU, investigating the specific weight of each dimension in a sample of young adults (N = 301; 82.7% females; Mage = 22.89; SD = 3.02). Participants completed a self-report questionnaire, including the Relationship Questionnaire, the Family Adaptability and Cohesion Evaluation Scale IV, and the Smartphone Addiction Scale. The regression and relative weight analyses results showed that preoccupied attachment style and disengaged, chaotic, and enmeshed family functioning were positively related to PSU. Implications for future research and interventions were discussed.